Association of energy drink consumption with substance-use initiation among adolescents: A 12-month longitudinal study. (February 2020) - Galimov, Artur; Hanewinkel, Reiner; Hansen, Julia; Unger, Jennifer B; Sussman, Steve; Morgenstern, Matthis
Background: Aggressive marketing has resulted in exponential growth of energy drink sales in recent years. Despite growing concerns about the negative health effects of energy drinks, they are increasingly popular among young people. Little is known about temporal associations between energy drink consumption and other drug use, though some researchers have suggested that energy drink consumption reflects an entry into a drug-using lifestyle. Aims: The purpose of this study was to evaluate whether energy drink use among adolescents who have never tried substances is associated with a risk of initiating tobacco (i.e. cigarettes, e-cigarettes, and hookah) and alcohol use. Methods: A school-based longitudinal study of 3071 adolescents ages 9–17 years was conducted in six federal states of Germany. Data analyses involved two assessment waves that took place approximately 12 months apart: baseline (fall-winter of school year 2016–2017), and 12-month follow-up (fall-winter of school year 2017–2018). Results: Multilevel models revealed that energy drink use at baseline was associated with cigarette (odds ratio for energy drink ever use, 3.15 (95% confidence interval, 2.07–4.78 )), e-cigarette (odds ratio, 4.32 (95% confidence interval, 2.87–6.51)), hookah smoking (odds ratio, 3.15 (95% confidence interval, 2.06–4.82)), and alcohol use (odds ratio, 2.26 (95% confidence interval, 1.75–2.93)) initiation within 12 months. Conclusions: These results raise the possibility that energy drinks may potentially act as a gateway drug to other substances. However, inferences regarding whether this association is or is not causal cannot yet be made.